Associated factors and impacts of sedentary behaviour in patients with heart failure: A longitudinal study. (October 2020) - Chen, Mei-Fang; Ke, Shin-Rong; Liu, Chih-Ling; Wu, Tao-Cheng; Yu, Ya-Mei; Chiou, Ai-Fu
Background: Sedentary behaviours may be related to factors such as self-efficacy, mood and social support. However, there is a paucity of longitudinal follow-up studies examining factors related to sedentary behaviour from physical-psychosocial perspectives in patients with heart failure. Aims: The purpose of this study was to explore the multidimensional associated factors and impacts of sedentary behaviour in heart failure patients. Methods: A longitudinal design was used. A convenience sample of 128 heart failure patients recruited from two large medical centres in northern Taiwan was obtained. Patients were interviewed with structured questionnaires to assess physical activity, symptom distress, exercise self-efficacy, anxiety and depression, social support, sleep quality and quality of life before discharge and at 3 and 6 months after discharge. Results: Heart failure patients reported low physical activity and tended to be sedentary. Sedentary behaviour was gradually reduced from hospitalization to 6 months after discharge. Sleep quality, quality of life, analgesic use, symptom distress and exercise self-efficacy were significant associated factors that explained 42.1–51% of the variance in sedentary behaviour. Patients with high sedentary behaviour had significantly greater depression and poorer sleep and quality of life than those with low sedentary behaviour at hospitalization and showed a significant improvement in depression at 3 and 6 months after discharge. Conclusion: Sedentary behaviour is common in heart failure patients and has impacts on depression and quality of life. An appropriate physical activity programme focusing on disease self-management and enhancing self-efficacy is needed for heart failure patients to improve their sedentary behaviour and quality of life.